2003
DOI: 10.2478/bf02476227
|View full text |Cite
|
Sign up to set email alerts
|

Analytical applications of electrode sensitive to labetalol in pharmaceuticals

Abstract: The analytical properties of an ion-selective electrode sensitive to labetalol with a liquid membrane, based on ion-pair complexes with sodium tetraphenylborate (TPBNa + ) are described. The studied electrode can be used for the determination of labetalol hydrochloride as a protonated form of labetalol in pharmaceuticals. The calibration curve, e.g. EMF=f(pC LabHC l ) is linear in the range from 10 ¡5 to 10 ¡2 mol L ¡1 with a correlation coe¯cient of 0.9992 and slope of 61.13 mV/decade, which is close to the N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…The data are consistent with a photooxidation process involving a hydroperoxide, as has been proposed for the oxidative photodecomposition of dichloromethane catalyzed by FeCl 4 − on Dowex and the oxidative photodecomposition of chloroform by homogeneous FeCl 4 − . As was proposed for those systems, the reaction can be expected to be initiated through photodissociation of a chlorine atom following excitation into a LMCT band . Hydrogen abstraction from the α‐carbon of the alcohol and the subsequent reaction of the hydroxyalkyl radical with oxygen yield a peroxy radical (R + is used to signify cation resin sites): )(normalRprefix+FeCl4hν0.25em)(Rprefix+FeCl3+0.25emnormalCnormall normalCnormall+0.25emnormalCnormalH3normalCnormalH2normalOnormalHnormalHnormalCnormall0.25emprefix+0.25emnormalCnormalH3normalCnormalHnormalOnormalH normalCnormalH3normalCnormalHnormalOnormalH0.25emprefix+0.25emO2normalCnormalH3normalCnormalH)(normalOnormalHnormalOnormalO…”
Section: Discussionsupporting
confidence: 83%
“…The data are consistent with a photooxidation process involving a hydroperoxide, as has been proposed for the oxidative photodecomposition of dichloromethane catalyzed by FeCl 4 − on Dowex and the oxidative photodecomposition of chloroform by homogeneous FeCl 4 − . As was proposed for those systems, the reaction can be expected to be initiated through photodissociation of a chlorine atom following excitation into a LMCT band . Hydrogen abstraction from the α‐carbon of the alcohol and the subsequent reaction of the hydroxyalkyl radical with oxygen yield a peroxy radical (R + is used to signify cation resin sites): )(normalRprefix+FeCl4hν0.25em)(Rprefix+FeCl3+0.25emnormalCnormall normalCnormall+0.25emnormalCnormalH3normalCnormalH2normalOnormalHnormalHnormalCnormall0.25emprefix+0.25emnormalCnormalH3normalCnormalHnormalOnormalH normalCnormalH3normalCnormalHnormalOnormalH0.25emprefix+0.25emO2normalCnormalH3normalCnormalH)(normalOnormalHnormalOnormalO…”
Section: Discussionsupporting
confidence: 83%
“…The therapeutic importance of LBT initiated several reports on its determination in formulations viz: spectrophotometry (4-7), spectrofluorimetry (8-13), HPLC (14)(15)(16)(17), HPLC-MS (18)(19)(20), capillary electrophoresis (21,22), and Voltammetry (23). LBT was also determined in pharmaceuticals using an ion selective electrode sensitive to LBT with a liquid membrane (24).…”
Section: Labetalolmentioning
confidence: 99%
“…[2][3][4] Literature survey revealed that various analytical techniques were employed to estimate the concentration of Lab in pharmaceutical preparations, either alone or in combination with hydrochlorothiazide, and in biological fluids. These techniques include spectrofluorimetry, [5][6][7][8][9][10] chromatography, [11][12][13][14][15][16][17][18] capillary electrophoresis, 19,20 capillary isotachophoresis, 21 NMR spectroscopy, 22 ion-selective electrode using ion-pair complex, 23 and adsorptive voltammetry, 24 methods which in comparison to proposed electrodes require sample manipulation, are affected by various interferences, inappropriate for colored or turbid solutions, and more expensive as they require sophisticated equipment and software for data processing.…”
Section: Introductionmentioning
confidence: 99%